Spatial attention based on 2D location and relative depth order modulates visual working memory in a 3D environment. - Fang, Wei; Wang, Kaiyue; Zhang, Ke; Qian, Jiehui (British Journal of Psychology, 2023)
The attentional effect on visual working memory (VWM) has been a heated research topic in the past two decades. Studies show that VWM performance for an attended memory item can be improved by cueing its two‐dimensional (2D) spatial location during retention. However, few studies have investigated the effect of attentional selection on VWM in a three‐dimensional setting, and it remains unknown whether depth information can produce beneficial attentional effects on 2D visual representations similar to 2D spatial information. Here we conducted four experiments, displaying memory items at various stereoscopic depth planes, and examined the retro‐cue effects of four types of cues – a cue would either indicate the 2D or depth location of a memory item, and either in the form of physical (directly pointing to a location) or symbolic (numerically mapping onto a location) cues. We found that retro‐cue benefits were only observed for cues directly pointing to a 2D location, whereas a null effect was observed for cues directly pointing to a depth location. However, there was a retro‐cue effect when cueing the relative depth order, though the effect was weaker than that for cueing the 2D location. The selective effect on VWM based on 2D spatial attention is different from depth‐based attention, and the divergence suggests that an object representation is primarily bound with its 2D spatial location, weakly bound with its depth order but not with its metric depth location. This indicates that attentional selection based on memory for depth, particularly metric depth, is ineffective.